1986
DOI: 10.1073/pnas.83.3.614
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-nonspecific replication of transfected plasmid DNA in poxvirus-infected cells.

Abstract: A system in which transfected plasmid DNA replicates in the cytoplasm of poxvirus-infected cells is described. A variety of recombinant plasmids was introduced into poxvirus-infected cells by transfection, and replication of input plasmid DNA was monitored by (i) digestion with restriction enzymes that discriminate between input methylated plasmid DNA and unmethylated DNA produced by replication in mammalian cells; (it) amplification of intracellular plasmid DNA; and (Wi) density shift analysis in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 31 publications
(33 reference statements)
3
41
1
Order By: Relevance
“…However, this could not explain the effects of the proteasome inhibitors since VACV-induced plasmid replication was also prevented by the addition of MG132. Previous studies had demonstrated the ability of transfected plasmids to replicate in the cytoplasm of poxvirus-infected cells (6,32). Importantly, plasmid replication requires each factor known to be required for VACV genome replication (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this could not explain the effects of the proteasome inhibitors since VACV-induced plasmid replication was also prevented by the addition of MG132. Previous studies had demonstrated the ability of transfected plasmids to replicate in the cytoplasm of poxvirus-infected cells (6,32). Importantly, plasmid replication requires each factor known to be required for VACV genome replication (10).…”
Section: Discussionmentioning
confidence: 99%
“…To test this model, we took advantage of previous observations that any circular DNA can be replicated in cells infected with poxviruses (6,32). Plasmid replication occurs in cytoplasmic viral factories and requires all viral proteins known to be necessary for VACV genome replication, making it a surrogate for the latter (10).…”
Section: Fig 6 Effect Of Time Of Mg132 Addition On Late Gene Expresmentioning
confidence: 99%
“…In Saccharomyces cerevisiae and some viruses, origins were identified as autonomous replication sequences that confer replication ability to transfected episomes (31). However, the autonomous replication strategy to define origins was unsuccessful when applied to poxviruses: plasmids regardless of sequence efficiently replicate in poxvirus-infected cells, raising questions of whether specific origins are needed for the viral replication machinery (14)(15)(16). To investigate the mechanism of VACV replication, we exploited approaches recently proven effective for mapping eukaryotic replication origins by deep sequencing (26,32).…”
Section: Consensus Nucleotides At the Start And End Of Vacv Dna Fragmmentioning
confidence: 99%
“…Collectively, these data are compatible with a discontinuous or semidiscontinuous mode of genome replication, with origins located near the termini. Subsequently, however, the existence of specific VACV origins came into question by the demonstration that any circular DNA replicates in VACV or Shope fibroma virusinfected cell cytoplasm, and that replication is not enhanced by inclusion of any VACV DNA sequence (14,15). Moreover, all VACV proteins known to be required for genome replication are also required for origin-independent plasmid replication (16).…”
mentioning
confidence: 99%
“…Second, one knows precisely where the CDV is located and need not make any assumptions regarding differential rates of CDV uptake and incorporation into DNA. Finally, poxviruses cannot replicate linearized plasmid DNAs that are transfected into infected cells unless they are first recombined into circles (10,12,64). Thus, the system we are studying becomes recombination dependent, since circularization, through recombination, must precede the replication of these DNAs.…”
mentioning
confidence: 99%